WEB-SAINSTREN (Science and Digital Disaster Literacy Website) to improving Knowledge and Disaster Preparedness of Islamic Boarding School Students - Nurul Hidayah; Pepin Nahariani; Anja Hesnia Kholis; Syahdatul Nabila Indana Zulfa; Abdul Azis (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2025)
Introduction: Islamic boarding schools as educational institutions still rarely carry out educational activities on disaster mitigation. The lack of knowledge about disasters among students makes the risk of fatalities due to disasters high. Objectives: to analyze the influence of WEB-SAINSTREN on the level of knowledge and disaster preparedness of students at Islamic boarding schools. Methods: Pre-Experimental with pre-posttest design approach. The population in this study were students of PP Al Muhibbin (male and female), PP Al Ma'arij (male and female) and PP Al Madienah (female). Using purposive sampling, the sample that met the inclusion and exclusion criteria was (n = 171). The research instrument consisted of four parts: Website, demographic sheet, disaster knowledge questionnaire and disaster preparedness questionnaire. Univariate analysis was conducted by calculating the mean, median, mode and creating a frequency distribution based on the category of each variable. Bivariate analysis used the Wilcoxon sign rank test. Results: almost half of the respondents (45.6%) were aged 13-15 years. more than half of the respondents were female (55%). most of the respondents were at secondary education level (SMA) (40.9%). more than half had never attended disaster education (56.7%). Conclusions: There is a significant influence of providing disaster education through websainstren on increasing knowledge and disaster preparedness of Islamic boarding school students.